1996
DOI: 10.1016/s0092-8674(00)81100-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure and Stability of the KH Domain: Molecular Insights into the Fragile X Syndrome

Abstract: The KH module is a sequence motif found in a number of proteins that are known to be in close association with RNA. Experimental evidence suggests a direct involvement of KH in RNA binding. The human FMR1 protein, which has two KH domains, is associated with fragile X syndrome, the most common inherited cause of mental retardation. Here we present the three-dimensional solution structure of the KH module. The domain consists of a stable beta alpha alpha beta beta alpha fold. On the basis of our results, we sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
275
2
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(288 citation statements)
references
References 41 publications
10
275
2
1
Order By: Relevance
“…The KH domain has been identified in a wide spectrum of RNA-binding proteins (Gibson et al+, 1993;Siomi et al+, 1993)+ Although this domain was initially identified as a repeated 45-amino-acid motif in hnRNP K (Siomi et al+, 1993), subsequent alignments and structural studies have defined a more extensive 68-72 residue KH "maxi domain" (Musco et al+, 1996)+ NMR spectroscopic and X-ray crystallographic analyses of a number of KH domains (Musco et al+, 1996(Musco et al+, , 1997Baber et al+, 1999;Lewis et al+, 1999;Wimberly et al+, 2000) have revealed that the initially described 45-residue core is configured as a baab unit+ The data further reveal two KH domain subtypes based on the more extensive structure: The type I KH domain (e+g+, KH-3 of hnRNP K) includes a C-terminal ba extension and the type II KH domain (e+g+, ribosomal protein S3) contains an N-terminal ab extension (Grishin, 2001)+ All three KH repeats within the PCBPs belong to the type I KH domain comprising a three-stranded antiparallel b-sheet packed against three a-helices ( baabba; Fig+ 2A)+ Two unstructured surface loops extend from this structure, one containing an invariant GXXG and a second of variable length and sequence+ These loops may be of central importance in determining nucleic acid binding specificity (Adinolfi et al+, 1999)+ An extended survey of PCBP gene organization including the inferred intron-exon organization of the genes encoding human FMR-1 (Eichler et al+, 1993), mouse quaking (Kondo et al+, 1999), Nova-1 and Nova-2, and KOC (known also as IGF-II mRNA-binding protein 3; Fig+ 2A) reveals that introns are restricted to positions between secondary structural segments of the KH domain+ This positioning suggests that the presentday KH domain may have arisen from a combination and assortment of mini-exons encoding individual structural elements+ This model would suggest that prokaryotic and eukaryotic KH domains might have evolved by convergent evolution of nucleic acid-binding modules (Graumann & Marahiel, 1996)+ The presence of multiple KH domains in each of the PCBPs brings up the question of which domain, or combination of domains, dictates RNA-binding specificity and affinity+ At present, there is no simple answer to this question+ Although individual KH domains from PCBPs can bind single-stranded nucleic acids (Dejgaard & Leffers, 1996), it is clear that the binding affinity and specificity of the intact protein reflects a 270…”
Section: The Multiple Kh Domains Of the Pcbps: Complex Correlations Tmentioning
confidence: 99%
“…The KH domain has been identified in a wide spectrum of RNA-binding proteins (Gibson et al+, 1993;Siomi et al+, 1993)+ Although this domain was initially identified as a repeated 45-amino-acid motif in hnRNP K (Siomi et al+, 1993), subsequent alignments and structural studies have defined a more extensive 68-72 residue KH "maxi domain" (Musco et al+, 1996)+ NMR spectroscopic and X-ray crystallographic analyses of a number of KH domains (Musco et al+, 1996(Musco et al+, , 1997Baber et al+, 1999;Lewis et al+, 1999;Wimberly et al+, 2000) have revealed that the initially described 45-residue core is configured as a baab unit+ The data further reveal two KH domain subtypes based on the more extensive structure: The type I KH domain (e+g+, KH-3 of hnRNP K) includes a C-terminal ba extension and the type II KH domain (e+g+, ribosomal protein S3) contains an N-terminal ab extension (Grishin, 2001)+ All three KH repeats within the PCBPs belong to the type I KH domain comprising a three-stranded antiparallel b-sheet packed against three a-helices ( baabba; Fig+ 2A)+ Two unstructured surface loops extend from this structure, one containing an invariant GXXG and a second of variable length and sequence+ These loops may be of central importance in determining nucleic acid binding specificity (Adinolfi et al+, 1999)+ An extended survey of PCBP gene organization including the inferred intron-exon organization of the genes encoding human FMR-1 (Eichler et al+, 1993), mouse quaking (Kondo et al+, 1999), Nova-1 and Nova-2, and KOC (known also as IGF-II mRNA-binding protein 3; Fig+ 2A) reveals that introns are restricted to positions between secondary structural segments of the KH domain+ This positioning suggests that the presentday KH domain may have arisen from a combination and assortment of mini-exons encoding individual structural elements+ This model would suggest that prokaryotic and eukaryotic KH domains might have evolved by convergent evolution of nucleic acid-binding modules (Graumann & Marahiel, 1996)+ The presence of multiple KH domains in each of the PCBPs brings up the question of which domain, or combination of domains, dictates RNA-binding specificity and affinity+ At present, there is no simple answer to this question+ Although individual KH domains from PCBPs can bind single-stranded nucleic acids (Dejgaard & Leffers, 1996), it is clear that the binding affinity and specificity of the intact protein reflects a 270…”
Section: The Multiple Kh Domains Of the Pcbps: Complex Correlations Tmentioning
confidence: 99%
“…Siomi et al 1994;Musco et al 1996), in the middle of Mis3, and the motif sequence is highly conserved in other eukaryotic homologues (locations indicated by the hatched boxes in B). The consensus sequence (Burd & Dreyfuss 1994) indicated in C is retained in Mis3.…”
Section: Mis3 Is a Highly Conserved Putative Rna-binding Proteinmentioning
confidence: 99%
“…34 -37). KH domains are invariably involved in the creation and/or stabilization of RNA-binding sites in multiple proteins (35)(36)(37). Physiological functions of these proteins have not been defined with precision, but they appear to play roles in mRNA processing, translocation, and translation (35)(36)(37).…”
Section: Figmentioning
confidence: 99%